Characterization of the outer membrane vesicles of the gastric pathogen Helicobacter pylori - Brown, Paul Alexander (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2011)
The aim of the present study was to investigate the structure and composition of H. pylori outer membrane vesicles (OMVs) and to functionally characterize several OMV-associated pathogenic activities. Initial studies focussed on the structural characterization of H. pylori OMVs based on electron microscopy and proteomic analyses. Having optimized growth conditions and an OMV isolation method this study demonstrated that the OMVs recovered comprised a heterogeneous mixture of vesicles 20-400 nm in diameter and exhibited apparent inter-strain variation with respect to their proteome. Mass spectrometry (MS) analysis confirmed that the process of vesiculation represents a selective mechanism of protein sorting, due to the enrichment of outer membrane and periplasmic proteins, consistent with the findings of others in relation to OMV production by different species of gram negative bacteria. In addition, H. pylori OMVs were shown to contain several known and potential virulence and immunomodulatory factors, including adhesins, CagA and VacA.
Keywords: Molecular Medicine, Ph.D.; Ph.D. Trinity College Dublin